Pulmonary function in children with atrial septal defect before and after heart surgery. Issue 5 (1st November 1998) - Šulc, J; Andrle, V; Hruda, J; Hučín, B; Šamánek, M; Zapletal, A
Abstract : Objective: To test the effect of heart disease and heart surgery on lung function. Design: A pulmonary function study of children undergoing surgery for atrial septal defect (ASD). Settings: University hospital. Patients: 26 children tested before surgery (at mean (SD) age 11.8 (3.8) years) and 24 patients tested 1.8 (0.2) years after surgical correction. Methods: Lung volumes, lung elasticity, and airway patency indices were measured using standard techniques. Results: Before surgery : pulmonary function test abnormalities were found in 18 of the 26 patients. Stiff lung was found in 12, lung hyperinflation in five, and indices of decreased airway patency in four. Total lung capacity decreased in only two patients. After surgery : pulmonary function test abnormalities were found in 12 of the 24 patients (informed consent not given for two patients). Stiff lung was detected in nine and indices of peripheral airway obstruction in four. Mean values of specific airway conductance and peak expiratory flow were all normal. Lung hyperinflation was found only in one of 24 patients. No correlation between perioperative events and pulmonary function test data was found. Conclusions: Pulmonary function test abnormalities persist in half the patients almost two years after surgery for ASD. A decrease in the total frequency of pulmonary function test abnormalities (in 19% of the patients), with a decrease in stiff lung in 8% and lung hyperinflation in 15%, was not significant. Impairment of lung function related to ASD is associated with the disease itself rather than the surgical procedure.